TOURISM IMAGE RECOVERY STRATEGY POST-NATURAL DISASTERS IN INDONESIA - Kurniasari, Nani; Haloho, Heppy N.Y.; Christian, Alvina Eunice (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019), 2019)
Tourism potential in Indonesia is a privilege that must be thankful for. However, that potential is not supported enough by the stability of the natural condition itself. Tourists destinations which is popular in Indonesia tend to be liable to the natural disasters. It happens recently in Bali and Lombok. A couple of natural disasters that afflict those two regions as the Indonesian tourism sector has an impact on reducing the number of foreign tourist to visit those tourists destinations. Based on the previous research studies, handling the natural disasters that occur in tourists destinations which are usually being visited by foreign tourist is a way more complex than the similar disasters which occur in the destinations that are only being visited by local tourists. The natural disasters which is involving foreign tousists will also have an impact on the bilateral relations between the two countries. In addition, the foreign media news wil have a wider impact on Indonesia’s image because of dealing with the natural disasters and the responsibilities to the victims. The government is still find some obstacles in dealing with a decreasing reputation after the natural disasters in Indonesia’s tourists destinations, even though the rapid response is correlated with the large amoun of costs that incurred to deal with the disasters. Then, formulating the right strategy for handling the post-natural disasters in Indonesia’s tourists destinations is important. This study aims to find the communication strategies which are needed to be the respons of the natural disasters that occur Indonesian tourism sector. Using the post-positivistic paradigm, this study was approached qualitatively and presented descriptively to reveal the right communication strategy on handling the Indonesia’s tourism sector which is affected by the natural disasters based on the situasional crisis communication theory. The interview was chosen as a data collection technique for the related sector. Open coding, axial coding, and selective coding was used as the data analysis technique. This research is expected to formulate the strategies for restoring the image of Indonesia’s tourism sector after the natural disasters. In fact, the research at this phase is still rarely done becuse the other similar research is still focus on the countermeasures during the disasters such as victim evacuation or the mitigation of the disasters.